Measuring candidate selection mechanisms in European elections: Comparing formal party rules to candidate survey responses. (March 2018) - Meserve, Stephen A; Palani, Sivagaminathan; Pemstein, Daniel
Students of party organization often rely on politicians' perceptions when measuring internal party institutions and organizational characteristics. We compare a commonly used survey measure of political parties' European Parliament candidate selection mechanisms to measures that the authors coded directly from parties' selection rules. We find substantial disconnect between formal institutions and survey respondent perceptions of selection mechanisms, raising questions about measure accuracy and equivalency. While this divergence may be driven either by distinctions between de jure and de facto selection procedures or by respondent error, we find the differences between the two measures are unsystematic. Our findings suggest that authors studying party characteristics must decide whether their research question calls for survey or formal institutional measures.